2014
DOI: 10.1007/s12602-014-9166-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Lactic Acid Bacteria Isolated from Water-Buffalo Mozzarella Cheese

Abstract: This study evaluated the probiotic properties (stability at different pH values and bile salt concentration, auto-aggregation and co-aggregation, survival in the presence of antibiotics and commercial drugs, study of β-galactosidase production, evaluation of the presence of genes encoding MapA and Mub adhesion proteins and EF-Tu elongation factor, and the presence of genes encoding virulence factor) of four LAB strains (Lactobacillus casei SJRP35, Leuconostoc citreum SJRP44, Lactobacillus delbrueckii subsp. bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 60 publications
0
26
1
2
Order By: Relevance
“…β‐galactosidase enzyme producing bacteria convert lactose into glucose and galactose. Lactose intolerance can be improved by consumption of functional foods with probiotics that produce β‐galactosidase enzyme (Jeronymo‐Ceneviva et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…β‐galactosidase enzyme producing bacteria convert lactose into glucose and galactose. Lactose intolerance can be improved by consumption of functional foods with probiotics that produce β‐galactosidase enzyme (Jeronymo‐Ceneviva et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it can be observed that L. curvatus P99 maintained its viability above 7.7 log CFU/ml. When evaluating species of Lactobacillus, for the passage to the simulated intestinal juice, several authors verified tolerance of the microorganisms when exposed to intestinal conditions (Jeronymo-Ceneviva et al, 2014;Ruiz-Moyano, Martín, Benito, Nevado, & de Guía Córdoba, 2008;Senter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, as have been conducted by Jose et al [33] and Liu et al [34], the lactobacilli tolerated and survived in MRS broth (pH: 3), while reduction in viability has been seen at pH 2. The Lactobacillus strains isolated from river buffalo milk cheese showed survivability in presence of NaCl (1–7%), indicating their high sodium chloride tolerance [35]. The buffalo milk probiotic isolates of L. fermentum and L. acidophilus survived luxuriously in presence of 1–6% NaCl, whereas moderate growth was seen at 7% concentration of NaCl [36].…”
Section: Discussionmentioning
confidence: 99%